2015
DOI: 10.3917/drs.091.0623
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Forms of Resistance to the Law: An Ethnographic Study of Street Vendors in Bogotá

Abstract: Distribution électronique Cairn.info pour Ed. juridiques associées. © Ed. juridiques associées. Tous droits réservés pour tous pays. La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 4 publications
2
16
0
1
Order By: Relevance
“…In non-shopping malls, such as a night markets, the situation is more vulnerable, especially in Malaysia, because most of the vendors are categorised in the B40 (bottom 40% of people), where their incomes are under 3000 MYR (700 US Dollars) per month. The research finding revealed that more than 65% of respondents are from the low-income group of the community, and the result is consistent with that of prior research in Vietnam [105], Colombia [102], Philippines [106], India [107], and Peru [108].…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In non-shopping malls, such as a night markets, the situation is more vulnerable, especially in Malaysia, because most of the vendors are categorised in the B40 (bottom 40% of people), where their incomes are under 3000 MYR (700 US Dollars) per month. The research finding revealed that more than 65% of respondents are from the low-income group of the community, and the result is consistent with that of prior research in Vietnam [105], Colombia [102], Philippines [106], India [107], and Peru [108].…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Therefore, a critical gap exists in the challenges of non-online shopping due to the COVID−19 pandemic that must be filled experimentally and theoretically [101]. The study is also important given its practical focus on vendors' attitudes and their receptiveness towards international tourists which is missing in the night market literature [17,102].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A number of studies have been conducted focusing on street vending subject across the world. These include (Bhowmik 2005;Williams and Gurtoo 2012;Vargas 2016;Mazhambe 2017) and many more. Such studies paid much of their focus on using street vending as a tool against poverty, causes of poverty, challenges facing poverty and a few studies focused on the components of street vendors.…”
Section: The Relationship Between the Study And The Existing Studiesmentioning
confidence: 99%
“…The second premise of this article is that organised and everyday resistance can be studied in relation to each other and everyday resistance in particular can be coordinated by organised actors. Studies on resistance often make a distinction between organised and everyday resistance (Scott, 1985Gutmann, 1993, Vargas and Urinboyev, 2015, Lilja and Vinthagen, 2018. Organised resistance is collective in nature and it is often associated with social movements, armed revolutionary groups, demonstrations, and riots (Tilly, 1991).…”
Section: Theoretical Framework: Exploring the Links Between Organised And Everyday Resistancementioning
confidence: 99%